STUDI KEMANFAATAN HUTAN BAGI MASYARAKAT HUTAN DESA SEMBELANGAAN KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Siti Maimunah; Andi M. Amin; Amrin Fauzi P. Lubis; Iskandar Iskandar; Pardi Yansah; Jay H. Samek (Jurnal Hutan Tropis, 2022)
PT. Bumitama Gunajaya Agro is a palm oil company that is committed to and contributes to sustainable economic development and conservation to help social forestry in Sembelangaan Village Forest. This partnership pattern can be an example of social forestry management that is expected by the Indonesia Government, namely multi-party support.The research methodology uses a method to assess biodiversity created by HCVF Network and WWF (https://hcvnetwork.org/library/forest-integrity-assessment-tool/). This method was created by USAID LESTARI with Michigan State University USA.  The results showed that of the 17 plots with a sampling intensity of 0.02 it is known that the average value of forest usefulness for the community is 27.24 categorized as forests is a mostly healthy forest. Habitat conditions include 10 wetlands, 16 streams, 4 seasonal flood forests, 6 natural wetlands, 17 springs, 8 burned grasslands, 11 partially slope topography, wildlife habitat, 1 cave, 7 waterfalls, 4 open pandan expanses and 12 large trees only in the field. Rare animals encountered 3 red gibbon, 1 marble cat, 9 birds, 10 eagles, 6 owls, 10 wild boar, 9 deer. The encounter in the form of 23 footprints, 36 heard the animals sound, 16 saw live animals, there were 7 nests, feathers and feces.Sembelangaan Forest provides 41 species of faunal flora that are directly beneficial to the community and 9 flora and habitats that benefit local culture and wisdom. These potentials can be developed for activities in Sembelangaan Village Forest that can be done together with PT BGA in forest conservation and improving community welfare